2021
DOI: 10.1016/j.ajic.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene compliance of healthcare workers before and during the COVID-19 pandemic: A long-term follow-up study

Abstract: Background :Information about the long-term effects of hand hygiene (HH) interventions is needed. We aimed to investigate the change in HH compliance (HHC) of healthcare workers (HCWs) once a data-driven feedback intervention was stopped, and to assess if the COVID-19 pandemic influenced the HH behavior. Methods :We conducted an observational, extension trial in a surgical department between January 2019–December 2020. Doctors (n=19) and nurses (n=53) were included and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
0
31
0
3
Order By: Relevance
“…This study's findings are in line with another Danish study comparing hand hygiene compliance before and during COVID-19. Stangerup et al, using the same electronic hand hygiene monitoring system, showed that hand hygiene compliance was lower during the COVID-19 pandemic (from October 2020 to December 2020) than during a before-COVID-19 study period (from January 2019 to April 2019); 34% versus 58% 16 . However, the before-COVID-19 study period was a nudging intervention, which might have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings are in line with another Danish study comparing hand hygiene compliance before and during COVID-19. Stangerup et al, using the same electronic hand hygiene monitoring system, showed that hand hygiene compliance was lower during the COVID-19 pandemic (from October 2020 to December 2020) than during a before-COVID-19 study period (from January 2019 to April 2019); 34% versus 58% 16 . However, the before-COVID-19 study period was a nudging intervention, which might have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…Improper use of PPE (eg, improper use of gloves due to the fear of contamination), and decrease hand hygiene compliance among HCPs potentially increased the risk of transmission of specific pathogens. 22 , 23 , 24 An increased rate of blood culture contamination during the pandemic may contribute to increased CLABSI rates. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Once continued glove use was no longer recommended, this embedded practice was difficult to change, and reduced hand hygiene contributed to the risk of transmission. Others have found a decline in hand hygiene compliance during this time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%